2017
DOI: 10.1017/s0007114517001088
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased fruit and vegetable consumption on selected macronutrient and micronutrient intakes in four randomised-controlled trials

Abstract: Fruit and vegetable (FV) intake is associated with reduced risk of a number of non-communicable diseases. Research tends to focus on antioxidants, flavonoids and polyphenols contained in FV as the main beneficial components to health; however, increasing FV may also alter overall diet profile. Extra FV may be substituted for foods thought to be less healthy, therefore altering the overall macronutrient and/or micronutrient content in the diet. This analysis merged dietary data from four intervention studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Notably, the between-group difference in fiber intake reached 3 g/day in favor of the FV group, which is in agreement with data previously reported on the impact of increased FV consumption on dietary nutrient intakes [29]. Additionally, a pooled data analysis showed that one portion increase in FV was associated with a modest increase in total energy intake [31], which was also further evidenced in our data of older men and women. However, this small increase in total energy intake was not accompanied by changes in either BMI or waist circumference, which is similar to what has been commonly reported in studies targeting increased FV intakes without further instructions to reduce overall energy intake [32].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the between-group difference in fiber intake reached 3 g/day in favor of the FV group, which is in agreement with data previously reported on the impact of increased FV consumption on dietary nutrient intakes [29]. Additionally, a pooled data analysis showed that one portion increase in FV was associated with a modest increase in total energy intake [31], which was also further evidenced in our data of older men and women. However, this small increase in total energy intake was not accompanied by changes in either BMI or waist circumference, which is similar to what has been commonly reported in studies targeting increased FV intakes without further instructions to reduce overall energy intake [32].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the dietary fibre in fruits may reduce the metabolic effects on appetite [86]. Fulton et al have recently reported that protein intake was not influenced by an increase of fruit intake, although consumption moment was not investigated in their study [87]. In comparison with timing of consumption, absence or presence of consumption of protein-rich foods such as dairy products, nuts or seeds appears to be stronger associated with the risk of lower protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of wild blueberries, a food source high in vitro antioxidant properties, has been associated with a diet-induced increase in ex vivo serum antioxidant status [2]. Epidemiological studies and associated meta-analyses strongly suggest that long-term consumption of diets rich in plant polyphenols offer protection against development of cancers, cardiovascular diseases, diabetes, osteoporosis and neurodegenerative diseases [3][4][5]. These diseases are often associated with oxidative stress, which is generated by an imbalance between the production of reactive oxygen species (ROS) and the antioxidant efficiency of the cells.…”
Section: Introductionmentioning
confidence: 99%